Pengaruh Pelatihan Dan Lingkungan Kerja Terhadap Kinerja Pegawai BPBD Kota Kediri - Meri Oktavia Sulaiman (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
This study is to analyze the impact of the training and working environment on employee performance in BPBD of Kediri. This study used a questionnaire with 46 employee in BPBD of Kediri as the sample. Using the multiple linear regression analysis for testing hypotesis by software SPSS 21.0 for windows. The results of this study concluded that the partial of the two independent variables, only the training programs that have a significant influence on employee performance. The working environment has no significant influence on employee performance, but the two independent variables simultaneously have a significant influence on variable employee performance